Educational practices and identity dilemmas within the muslim minority of Thrace (Greece): the case of Xanthi - Νοταράς Ανδρέας (The Greek Review of Social Research, 2016)
This article examines the educational practices of the Muslim Minority in Thrace (Greece) in relation to subsequent identity dilemmas. The abrogation of restriction policies against the minority and the affirmative action taken by the Greek State in the mid-nineties have led to new, more diversified educational practices. Minority schools are no longer considered as the only obvious choice for parents. State Greek-language schools gain constantly in popularity among the minority, especially in the town of Xanthi. I here bring forward the qualitative and quantitative features of this evolution and analyze the main dilemma between social strategies of integration and the concern for the preservation and reproduction of minority identity and its cultural content.